PENGEMBANGAN LEMBAR KERJA SISWA (LKS) BERBASIS GROUP INVESTIGATION (GI) PADA MATERI SISTEM PERNAPASAN DI KELAS VIII SMP NEGERI 4 PEMATANG SIANTAR - Adawiyah, Hafizhotu; Wilson Sitopu, Joni; Huda, M. Komarul (Program Studi Pendidikan Biologi, Fakultas Keguruan Dan Ilmu Pendidikan Universitas Simalungun, 2023)
This research is motivated by the teacher-centered learning model at SMP Negeri 4 Pematang Siantar, where students only listen to the teacher's explanations, resulting in inactivity during the lesson. This is partly due to the limited learning resources used. The learning resources used are only textbooks. Assignments, limited to textbooks alone, result in unstructured assignments for students. This study aims to produce a valid and practical Group Investigation-based Student Worksheet (LKS). The type of research used in this study is Research and Development (R&D). The development model used is the 4-D model: define, design, develop, and disseminate. Data collection techniques were carried out through validation, observation, questionnaires, and interviews. The research instruments used were validation sheets, observation sheets, questionnaires, and interview guidelines. The validation sheets and questionnaires were analyzed by finding percentages, while the results of observations and interviews were analyzed using descriptive techniques. Based on the research conducted, it was found that the Group Investigation-based Student Worksheet was declared very valid by the validator with a percentage of 82.14%. The practicality test results from the student response questionnaire were categorized as very practical with a score of 83%, and the teacher response questionnaire was categorized as practical with a score of 78.3%.